Variasi Sapaan Masyarakat Multikultural di Rokan Hilir Riau: Kajian Sosiodialektologi - Yusnidar, Lira; Suryadi, Muhammad (Universitas Muhammadiyah Surakarta, 2024)
This research aims to identify the lexical variations of address terms in Rokan Hilir Regency, RiauProvince, and the social factors influencing these terms, as well as to observe the characteristics of thelocal Malay community regarding their openness to other ethnic groups. This study is a descriptivequalitative research using a sociodialectological approach. The data in this research consist ofutterances obtained from conversations or communicative acts in various formal and informaldomains within the research area. Data collection methods include observation and monitoring of dailyinteractions and activities in the research area. The techniques used are note-taking and recording,which involve: 1) transcribing spoken data into written form according to the data obtained fromobservations, 2) identifying the variations of address terms used and the social factors influencingthese variations, 3) examining the values of the Malay ethnic group as the native community inaccepting other migrating ethnic groups, and 4) drawing conclusions. The results show that thevariations of address terms in Rokan Hilir Regency, Riau Province, originate from the Malay, Minang,Batak, and Javanese ethnic groups. The social factors underlying this include mutual respect, age, andfamiliarity, all of which refer to the overall harmony in society created through well-establishedrelationships. Additionally, the local community, particularly the Malay ethnic group, exhibits positiveattitudes such as openness, respect, and inclusiveness, which are reflected in the management ofnatural resources often handled by outsiders, Riau's status as a transmigration area, and theadaptability of the Malay language, which has become the lingua franca and the precursor to theIndonesian language.